Remote Sensing for Sustainable Development: Multi-Temporal Landsat Analysis of Land-Use Change and Urbanization in the Rejoso Watershed (2005–2024) - Alyavara Mayang Ferynandari; Ery Suhartanto; Linda Prasetyorini (Jurnal Penelitian Pendidikan IPA, 2026)
Rapid urbanization and shifting agricultural practices are reshaping watershed sustainability in Indonesia, yet their spatial and hydrological implications in the Rejoso Watershed (East Java) remain insufficiently quantified. This study evaluates land-use/land-cover (LULC) dynamics over 2005–2024 using multi-temporal Landsat imagery from five observation years (2005, 2011, 2015, 2020, and 2024). A hybrid classification (ISODATA clustering combined with visual interpretation) was validated using 250 ground points and confusion matrix metrics (overall accuracy and Kappa). Vegetation declined from 54.72% (197.11 km²) in 2005 to its minimum in 2020 at 38.06% (137.09 km²), then recovered to 41.28% (148.70 km²) in 2024. Agricultural land expanded from 32.14% (115.77 km²) to 52.28% (188.32 km²) in 2020 before contracting to 46.96% (169.14 km²) in 2024, indicating a notable post-2020 trend reversal with vegetation regrowth and reduced cropland extent. Built-up areas increased steadily (4.14% to 7.54%), while open land fluctuated and water bodies remained <1% with a slight decline. The 2020 map achieved the highest accuracy (95.83%; κ=0.96). These findings highlight upstream LULC reconfiguration and continued downstream urbanization, supporting integrated watershed management, upland rehabilitation, and stricter spatial planning.